Different scales determine the occurrence of aquatic macrophyte species in a tropical stream - Mori, Gisele Biem [UNESP]; Piedade, Maria Teresa Fernandez; Lopes, Aline; Ferraz, Silvio Frosini de Barros; Cancian, Leonardo Farage [UNESP]; Camargo, Antonio Fernando Monteiro [UNESP] (FapUNIFESP (SciELO), 2021)
Distributions of aquatic macrophyte species are commonly associated with water chemistry characteristics. However, other environmental factors that can lead to the occurrence of aquatic plants in lotic ecosystems, such as dynamic habitats linked to the surrounding landscape, have been underestimated. This study aims to evaluate landscape features that may influence the occurrence of species of euhydrophyte aquatic macrophytes in a tropical river basin. We assessed the occurrence of the following seven species: Egeria densa, Cabomba furcata, Potamogeton pusillus, Potamogeton polygonus, Utricularia foliosa, Pistia stratiotes and Salvinia molesta. We also measured environmental variables related to three spatial scales, local (limnological), channel and riparian landscape, along 25.5 Km of the Itanhaém River basin (São Paulo, Brazil). We found that local (limnological) and channel characteristics were important variables in determining the occurrence of aquatic macrophyte species while the landscape scale had little influence on species composition. Channel depth and margin slope were especially relevant abiotic variables in explaining the occurrence of four of the species but not P. pusillus, P. polygonus and U. foliosa. Our results highlight the importance of channel morphology for understanding aquatic plant occurrence and community composition in tropical rivers.
Keywords: Aquatic plants; Environmental gradients; Landscape; Lotic ecosystems; Riparian vegetation